Building Integrated Transparent Photovoltaic as a Strategy Towards Net Zero Energy Building in the Tropics: Considerations, Approach, and Feasibility based on Energy Performance - Susan, Susan; bin Zakaria, Safial Aqbar (Enquiry The ARCC Journal for Architectural Research, 2024)
Previous studies have found the potential of Building Integrated Photovoltaic (BIPV) implementation on vertical facades. The implementation was suggested for buildings with a minimum of 45 percent window-to-wall ratio (WWR). This number is quite challenging for tropical buildings where the suggested WWR ranges around 20 to 40 percent. Furthermore, the installation may appear less efficient due to the lower irradiance received on tropical vertical facades. Given the abundance of vertical facades in tropical high-rise buildings, there exists an opportunity to offset power reduction. Therefore, this study aims to determine the feasibility, influencing factors, and approach for installing building-integrated thin film transparent photovoltaics (BITPV) in tropical regions, focusing on energy production. The objective is achieved through a combination of literature review and simulation. Three layout configurations on three different geographical locations, which present a typical classroom module for school buildings, are observed. Treatment is applied based on orientation, WWR, and the cell coverage ratio. The feasibility is shown by at least 23 percent energy substitution promoted by several configurations. East is suggested for classrooms with 1:1 and 3:2 modules, while north is suggested for classrooms with 2:3 modules. For buildings with minimum WWR (20 percent), TPV installation with ≥40 percent cell coverage ratio (on the specified orientation) is suggested to achieve the mixenergy use target. Additionally, this study presents the influencing factors and design approach for BITPV to provide a comprehensive understanding of the subject.